Assessment of physicochemical characteristics and some heavy metals of Ossiomo River, Ologbo – a tributary of Benin River, Southern Nigeria - S.O. Ikhuoriah; C.G. Oronsaye (Journal of Applied Sciences and Environmental Management, 2016)
Assessment of the physicochemical characteristics and some heavy metals of Ossiomo River, Ologbo- a tributary of Benin River, Southern Nigeria was carried out from April 2012 to December 2012. Three stations were studied from upstream to downstream with a distance of about 2 kilometres between each station. A total of twenty-two (22) physicochemical parameters and some heavy metals were studied. Air temperature ranged from the mean 27.01 to 29.57°C, water temperature 25.87 to 27.56°C, depth 1.32 to 1.705m, flow velocity 0.08 to 0.13m/s, transparency 1.01 to 1.30m, pH 5.76 to 6.01, electrical conductivity 62.03 to 70.11μS/cm, turbidity 3.97 to 4.39 NTU, total suspended solid 5.01 to 5.80mg/l, total solid 38.82 to 42.11mg/l, total dissolve solid 29.60 to 33.84mg/l, DO 7.12 to 7.54mg/l, BOD5 1.51 to 2.60mg/l, alkalinity 48.63 to 53.28mg/l, the cations (sodium 1.35 to 1.43mg/l, potassium 0.25 to 0.26mg/l, calcium 0.92 to 1.00mg/l, magnesium 0.44 to 0.52mg/l), chloride 26.44 to 36.39mg/l, and the nutrient components (phosphorus 0.25 to 0.33mg/l, nitrate 0.16 to 0.20 mg/l, sulphate 0.88 to 0.94mg/l). Heavy metals level were generally low ranging from 0.05 to 2.61mg/l (cadmium 0.05 to 0.51mg/l, lead 0.06 to 0.09mg/l, zinc 0.11 to 0.12mg/l, copper 0.39 to 0.41mg/l, iron 2.00 to 2.61mg/l. Mean across stations were compared using Analysis of Variance and only three characteristics namely, air temperature, water temperature and flow velocity were significant. In station 1 (upstream), air temperature and water temperature were significantly higher than other 2 stations (downstream) while the flow velocity was significantly faster in station 3 than both upstream and midstream stations. A marked seasonal significant faster flow velocity was recorded in the wet than in the dry season. Furthermore, a significant (P < 0.05) pattern of seasonal variation was observed in seven (7) characteristics, total solids, calcium, magnesium, chloride, phosphate, nitrate and sulphate. Anthropogenic activities had negatively impacted on station 2 of the river, although the recorded values were still within acceptable limits.